The Influence of Muzaki's Trust on the Use of QRIS as an Instant Zakat Payment Tool at Baznas of North Sumatera Province - Ningsih Ningsih; Syahrul Amsari (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze the effect of muzaki trust on the use of QRIS (Quick Response Code Indonesian Standard) as a means of paying zakat, infaq, and sadaqah (Instant) at the National Amil Zakat Agency (BAZNAS) of North Sumatra Province. Muzaki trust is an important factor in determining the success of digital technology implementation in zakat management, especially in the era of digital transformation that demands transparency, convenience, and transaction security. This study uses a quantitative approach with survey and questionnaire methods involving 86 respondents. Data analysis was conducted using simple linear regression to examine the effect of trust dimensions, including integrity, competence, and reliability of digital systems, on muzaki's interest and decision in using QRIS. The results showed that muzaki trust significantly positively influences the use of QRIS as a payment method for Istan. These findings suggest that increasing muzaki trust through education, system transparency, and better digital services can strengthen the acceptance of digital payment technology within zakat institutions. This research is expected to be a reference for BAZNAS and other zakat management institutions in developing a more effective and trustworthy zakat digitization strategy.